Transformasi Bimbingan dan Penyuluhan Islam di Era Digital: Peluang dan Tantangan bagi Konselor Muslim - Apriani Apriani; Ibnu Hajar; Abd Rahman; Nurlailah Nurlailah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The digital era has brought significant changes to various aspects of life, including the field of Islamic guidance and counseling. Advances in information technology have opened new opportunities for Muslim counselors to expand their service reach and enhance the effectiveness of guidance through digital media. However, these developments also present several challenges, such as ethical issues, source authenticity, and the degradation of personal relationships between counselors and clients. This study aims to analyze the forms of transformation in Islamic guidance and counseling in the digital era, as well as to identify the opportunities and challenges faced by Muslim counselors. The research employs a library research method with a descriptive qualitative approach. The results indicate that digital transformation has shifted the paradigm of Islamic guidance from traditional face-to-face methods to a more flexible and interactive technology-based approach. Nevertheless, Muslim counselors are still required to uphold spiritual values, ethical principles, and the authenticity of Islamic teachings throughout the guidance process.